2006
DOI: 10.1007/s00122-006-0217-2
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of yield traits in an advanced backcross population derived from a cultivated Andean × wild common bean (Phaseolus vulgaris L.) cross

Abstract: Advanced backcross QTL analysis was used to identify quantitative trait loci (QTL) for agronomic performance in a population of BC2F(3:5) introgression lines created from the cross of a Colombian large red-seeded commercial cultivar, ICA Cerinza, and a wild common bean accession, G24404. A total of 157 lines were evaluated for phenological traits, plant architecture, seed weight, yield and yield components in replicated trials in three environments in Colombia and genotyped with microsatellite, SCAR, and phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
175
1
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(205 citation statements)
references
References 51 publications
21
175
1
8
Order By: Relevance
“…Similar estimates have been observed in other crops (Morrell et al 2005;Caldwell et al 2006;Liu and Burke 2006;Zhu et al 2007). Wild common bean is divided into two gene pools (Singh et al 1991a(Singh et al , 1991bBlair et al 2006;Díaz and Blair 2006;McClean et al 2004;McClean and Lee 2007;Rossi et al 2009) that appear to have arisen from a common ancestor 110 000 years BP (S. Mamidi, M. Rossi, D. Annam, S. M. Moghaddam, R. K. Lee, R. Papa, P. E. McClean, unpubl. data).…”
Section: A Model For Domestication In Common Beansupporting
confidence: 57%
“…Similar estimates have been observed in other crops (Morrell et al 2005;Caldwell et al 2006;Liu and Burke 2006;Zhu et al 2007). Wild common bean is divided into two gene pools (Singh et al 1991a(Singh et al , 1991bBlair et al 2006;Díaz and Blair 2006;McClean et al 2004;McClean and Lee 2007;Rossi et al 2009) that appear to have arisen from a common ancestor 110 000 years BP (S. Mamidi, M. Rossi, D. Annam, S. M. Moghaddam, R. K. Lee, R. Papa, P. E. McClean, unpubl. data).…”
Section: A Model For Domestication In Common Beansupporting
confidence: 57%
“…Esses marcadores podem ser utilizados na seleção de genótipos superiores. Embora inúmeros QTL já tenham sido identifi cados para vários caracteres na maioria das culturas de grande importância, inclusive alguns para a produção de grãos em feijão-comum (Faleiro et al, 2003;Melo et al, 2004;Rodrigues, 2004;Teixeira, 2004;Blair et al, 2006b), são poucos os relatos de sucesso da incorporação dessas informações ao processo seletivo e na obtenção de novas cultivares (Yousef & Juvick, 2001;Moreau et al, 2004;Bernardo, 2008).…”
Section: Introductionunclassified
“…However, Maxwell et al (2007) identified this marker in LG 9, evaluating the RIL G122/CO72548 population. This marker is also related to the QTLs for days to flowering, pods per plant, and 100 seed weight (Blair et al, 2006). In this study, the BM184 marker identified a QTL affecting increasing resistance to white mold at a distance of 3.34 cM from the QTL.…”
Section: Discussionmentioning
confidence: 67%
“…This same marker, according to Blair et al (2006), flanks QTLs for days to flowering, plant height, plant width, and number of seeds per plant and for the V gene for flower color. In this study, the BM187 marker identified the most significant QTL for the effect of reducing resistance to white mold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation